PENGEMBANGAN SMART SERVICE VILLAGE SYSTEM (SSVS) DALAM MENDUKUNG SMART GOVERNANCE MENGGUNAKAN METODE PERSONAL EXTREME PROGRAMMING - M. Ihsan Alfani Putera Putera; Nur Fajri Azhar; Syamsul Mujahidin (Universitas Islam Balitar, 2021)
To realize a Smart City, the government applies the use of technology in various aspects, one of which is in the public service sector in supporting smart governance by creating a Smart Service Village System (SSVS). One of the systems developed is the Balikpapan City Housing and Settlement Service in charge of carrying out government affairs in the areas of housing, settlements, landscaping and cemeteries. One of the existing fields, namely the housing sector, has a program of providing sanitation assistance and uninhabitable houses to the people of the city of Balikpapan. In its implementation, several obstacles were found, such as the slowness of data on recommendations for aid recipients, ineffective data management, and unclear process transparency. Therefore, a system was created that assists in collecting data on prospective beneficiaries, providing actual and fast progress, as well as a more optimal process of assisting. This SSVS development uses the Personal Extreme Programming method with seven phases, namely Requirements, Planning, Iteration Initialization, Design, Implementation, System Testing, and Retrospective. It is hoped that the existence of SSVS can help the implementation of aid provision more effectively, efficiently, and transparently. This research produces a web-based system with a total of 44 use cases that are carried out in 5 iterations. Testing is carried out by user training to see acceptance from related users. user training is carried out with 3 parties to represent several types of users, from the three parties it shows very good satisfaction and acceptance with a percentage of 100%.